2015
DOI: 10.1111/jsap.12350
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reaction during epirubicin infusion in a cat

Abstract: LETTERWhile the risk, is deemed low, cats should be monitored closely for infusion-related reactions when epirubicin is administered as hypersensitivity reactions can be serious and require urgent intervention. It may also be prudent to consider a slower rate of drug infusion. If a reaction occurs then drug administration should be discontinued and treatment with H1-antagonists, corticosteroids and/or adrenaline given, depending on severity. Infusion could be continued if the reaction was mild and the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Moreover, there were no allergic reactions or cardiotoxicity during transarterial infusion with raltitrexed, and no studies to date have reported any adverse events in this context. In contrast, allergic reactions and cardiotoxicity frequently occur when antitumor drugs such as oxaliplatin and epirubicin are used [ 10 , 21 - 23 ]. These results indicate that the combination of raltitrexed and oxaliplatin in TACE in patients with unresectable HCC is safe and tolerable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were no allergic reactions or cardiotoxicity during transarterial infusion with raltitrexed, and no studies to date have reported any adverse events in this context. In contrast, allergic reactions and cardiotoxicity frequently occur when antitumor drugs such as oxaliplatin and epirubicin are used [ 10 , 21 - 23 ]. These results indicate that the combination of raltitrexed and oxaliplatin in TACE in patients with unresectable HCC is safe and tolerable.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Previous reports of suspected HRs to pharmaceuticals in veterinary medicine include dexamethasone, 4 ophthalmic medication 5 and human albumin 6 among others. 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Previous reports of suspected HRs to pharmaceuticals in veterinary medicine include dexamethasone, 4 ophthalmic medication 5 and human albumin 6 among others. 7,8 HRs to insulin have been rarely reported in human medicine. [9][10][11]12 To our knowledge, an HR to insulin has not been previously reported in the veterinary literature.…”
Section: Introductionmentioning
confidence: 99%